Improving Digital Literacy Among Islamic Religious Education Teachers Through Online Training in Talaud Islands Regency - Sahabuddin; Ahdar; Muzakkir; Mardia; Fidrayani (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study analyzed: (1) the implementation of online training for Islamic Religious Education (IRE) teachers; (2) teachers' digital literacy following the training and its application in classroom instruction; and (3) the supporting and constraining factors affecting the implementation of online training and teachers' digital literacy in Talaud Islands Regency. A descriptive qualitative approach was employed, with thirteen informants selected through purposive sampling, including six IRE teachers, the Head of the Ministry of Religious Affairs Office, an IRE supervisor, one principal, and four students. Data were collected through semi-structured interviews, observations, and document analysis and were analyzed using the Miles and Huberman interactive model. The trustworthiness of the findings was enhanced through source and method triangulation and member checking. The findings revealed that online training was delivered through webinars, workshops, technical guidance programs, distance education, and independent digital learning. The training covered instructional planning, curriculum implementation, interactive learning media, digital assessment tools such as Quizizz and Google Forms, and digital literacy competencies. Zoom Meetings was the most frequently used platform, although teacher participation remained uneven. Teachers' digital literacy improved across information access, digital platform utilization, digital media development, digital assessment, digital ethics, and technology integration in IRE instruction. However, teachers' levels of digital literacy varied and were influenced not only by online training but also by self-directed learning, teacher professional education programs, teacher working groups, professional learning communities, and peer support. Supporting factors included teachers' motivation, institutional support from schools, the Ministry of Religious Affairs, and supervisors, as well as the availability of technological facilities. The primary constraints included unstable internet connectivity, limited access to digital devices, inadequate digital competencies, and inconsistent institutional support across different areas.